Patch testing with the Japanese baseline series 2015: A 4‐year experience. (4th January 2022) - Ito, Akiko; Suzuki, Kayoko; Matsunaga, Kayoko; Yagami, Akiko; Ito, Takashi; Tamagawa‐Mineoka, Risa; Adachi, Atsuko; Sugiura, Mariko; Miyazawa, Hitoshi; Kato, Atsuko; Nakada, Tokio; Nishioka, Kazue; et al.
Abstract: Background: The Japanese baseline series (JBS), established in 1994, was updated in 2008 and 2015. The JBS 2015 is a modification of the thin‐layer rapid‐use epicutaneous (TRUE) test (SmartPractice Denmark, Hillerød, Denmark). No nationwide studies concerning the TRUE test have previously been reported. Objectives: To determine the prevalence of sensitizations to JBS 2015 allergens from 2015 to 2018. Methods: We investigated JBS 2015 patch test results using the web‐registered Skin Safety Care Information Network (SSCI‐Net) from April 2015 to March 2019. Results: Patch test results of 5865 patients were registered from 63 facilities. The five allergens with the highest positivity rates were gold sodium thiosulfate (GST; 25.7%), nickel sulfate (24.5%), urushiol (9.1%), p‐ phenylenediamine (PPD; 8.9%), and cobalt chloride (8.4%). The five allergens with the lowest positivity rates were mercaptobenzothiazole (0.8%), formaldehyde (0.9%), paraben mix (1.1%), mercapto mix (1.1%), and PPD black rubber mix (1.4%). Conclusions: Nickel sulfate and GST had the highest positivity rates. The JBS 2015, including a modified TRUE test, is suitable for baseline series patch testing. Abstract : Patch test results of the Japanese baseline series 2015 from 2015 to 2018 for 5865 patients. The five allergens with the highest positivity rates were gold sodium thiosulfate, nickel sulfate, urushiol, p ‐phenylenediamine, and cobalt chloride.